(a+b)2-(a+b)(a-b)-(2b-1)(a+b) 其中a等于负3分之1 b等于3分之2怎么算
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 23:37:02
(a+b)2-(a+b)(a-b)-(2b-1)(a+b)其中a等于负3分之1b等于3分之2怎么算(a+b)2-(a+b)(a-b)-(2b-1)(a+b)其中a等于负3分之1b等于3分之2怎么算(a
(a+b)2-(a+b)(a-b)-(2b-1)(a+b) 其中a等于负3分之1 b等于3分之2怎么算
(a+b)2-(a+b)(a-b)-(2b-1)(a+b) 其中a等于负3分之1 b等于3分之2怎么算
(a+b)2-(a+b)(a-b)-(2b-1)(a+b) 其中a等于负3分之1 b等于3分之2怎么算
(a+b)2-(a+b)(a-b)-(2b-1)(a+b)
=a²+2ab+b²-(a²-b²)-2ab-2b²+a+b
=a+b
=-1/3+2/3=1/3
(a+b)2-(a+b)(a-b)-(2b-1)(a+b) =a^2+2ab+b^2-a^2+b^2-2ab-2b^2+a+b=a+b=-1/3+2/3=1/3
a+b=1/3
a-b=-1
2b-1=1/3
带入就好了
(a+b)2-(a+b)(a-b)-(2b-1)(a+b)=(1/3)2-1/3*(-1)-1/3*1/3
=1/9+1/3-1/9
=1/3
(a+b)^2-(a+b)(a-b)-(2b-1)(a+b)
=a^2+2ab+b^2-a^2+b^2-2ab+a-2b^2+b
=a+b
=1/3+2/3
=1
-2a(a+b)+b(a+b)
(a+2b)(a-2b)+(a-b)(a+b)-2(a-3b)(a-b)
5(a*a*b-3*a*a*b)-2*(a*a*b-7*a*b*b)
-a-b+2b^2/a+b
化简:|a+b|+|b-a|+|2b|
|a+b|-|b-a|+|2b|化简哦!
a-b+2b²/a+b
通分a-b,2b^/a+b
化简(2a-b/a+b-b/a-b)除以a-2b/a+b
计算:((a+b)(a-b)-(a-b)^2+2b(a-b))/4(a-b)
化简(2a-b/a+b-b/a-b)除以a-2b/a +b
化简:{[(2a-b)/(a+b)]-[b/(a-b)]}÷[(a-2b)/(a+b)]
计算·[(2a+-b)/(a+b)-b/(a+b)]/(a-2b)/(a+b)
(a-b)(a+b)²-(a+b)(a-b)²+2b(a²+b²)
(a-b)(a+b)²-(a+b)(a-b)²+2b(a²+b²)
(2a-3b)[(a+b)-b(a-3b)]
化简:a-[b-2a-(a-b)]
化简(2a-b/a+b-b/a-b)÷a-2a/a-b